An extension on INAR models with discrete Laplace marginal distributions. Issue 12 (18th June 2017) - Djordjević, Miodrag S.
ABSTRACT: The main theme considered in this article is an integer-valued thinning operator with both positive and negative values, its properties, and a new time series with skew discrete Laplace marginals. Some properties of this model are discussed, as well as estimators of unknown parameters, similarities and differences with some other existing models, applications in real-life situations, and identification and approximation of latent processes affecting the concerning process.